Online Malaysia Cup Ticketing System (OMaCTS) / Norul Faizah Ismail and Mohd Talmizie Amron - Ismail, Norul Faizah; Amron, Mohd Talmizie (2016)
Technology is developing rapidly nowadays. Thus, online shopping in business industry has become the new approach for companies to gain more benefits. E-commerce is a platform that has a very large market network. In recent years, online ticket sales for football are implemented to facilitate customers to purchase the tickets, but the tickets will be sold and distributed only at the final stage of the match. Football fans need to queue up at the counter to purchase the tickets. Having to queue up for tickets is time consuming and it often creates inadvertent stress among the football fans. The staffs at the stadium face many challenges to manage the ticket sales at the counter when the tickets are sold out while the fans are still queuing. Such frustration may lead to unforeseen calamities. In this work, I propose Online Malaysia Cup Ticketing System (OMaCTS) to give benefits to the organization and football fans. The system provides facilities for customers to make the ticket reservations online and print out their tickets by themselves. The methodology used in the development process is waterfall model which consists of five phases. The evaluation for users is categorized into six construct which are usability, trust, ease of use, understandability, efficiency, and interface. The result shows that most users are satisfied with the interface of OMaCTS with the highest mean of 4.61 (SD = 0.487).